Suboptimal engagement of high-level cortical regions predicts random noise-related gains in sustained attention - Harty, S; Cohen Kadosh, R (SAGE Publications, 2019)
Inter-individual variability in outcomes across individuals poses great challenges for the application of non-invasive brain stimulation in psychological research. Here, we examine how the effects of high-frequency transcranial random noise stimulation (tRNS) on sustained attention vary as a function of a well-studied electrocortical marker, spontaneous theta/beta ratio. Seventy-two subjects were administered sham, 1mA, and 2mA tRNS in a double-blind, cross-over manner, while performing a sustained attention task. 1mA was associated with improved sustained attention, whereas the effect of 2mA was similar to sham. Furthermore, individuals’ baseline theta/beta ratio moderated the effects of 1mA tRNS, and provided explanatory power over and beyond baseline behavioural performance. The tRNS-related effects on sustained attention were also accompanied by reductions in theta/beta ratio. These findings impart novel insights into mechanisms underlying tRNS effects, and emphasize how designing studies that link variability in cognitive outcomes to variability in baseline neurophysiology can improve inferential power in neurocognitive research.